Rehiring, Seniority, and Labor Force Adjustment - Santiago, Carlos E. (Journal of Labor Economics, 1987)
This paper examines the role of seniority in two interrelated phenomena-rising age-earnings profiles and the use of layoffs rather than wage adjustments during economic decline. The results suggest that rehiring based on a seniority-first criterion is not inconsistent with an approach that maximizes worker productivity within a heterogeneous labor force. Moreover, assessment of worker reliability based on the upward portion of the wage-productivity cum seniority locus is appropriate since it reduces subsequent turnover. Thus, an approach that combines human capital accumulation with Lazear-type deferred payments schemes explains much of long-term worker-firm attachment.